ANALYSIS ON MOTIVATION IN ENGLISH LEARNING THROUGH ICE BREAKING METHOD AT MADRASAH IBTIDAIYAH SYABABUL QORIB - Novita, Novita andini; Nurlaili; Zulfitri (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This research was conducted to analysis the students motivation with ice breaking at Madrasah Ibtidaiyah Syababul Qorib Perbaungan 2023/2024 in academic year which consisted of 29 students. This research used qualitative method. Teaching activities are not only limited to the teacher providing material but also pay attention to students whether they are focused or not during the learning process. The presence of internal and external factors is very important so that the learning process is good and enjoyable. Low learning motivation makes learning not optimal. Students are not focused and enthusiastic because teachers often use the lecture method in the learning process. So that students can focus again, ice breaking is needed to restore a pleasant learning atmosphere. Ice breaking functions as a learning process, as an energizer before providing the main material, ice breaking , and when experiencing boredom, it gives a pleasant impression when learning. Examples of ice breaking include providing quizzes, games, singing and others that make learning more fun. The objectives of this research are (1) Analysis learning motivation in the face-to-face learning process, (2) Analysis student learning motivation through the use of ice breaking in learning. In collecting the data, researcher distributed interview and ice breaking (sing a song) to measure their motivation in learning English, and the researcher used opposite-word song as a ice breaking and it is categorized into good motivation because the students very excited to learning English. Based on the research finding, it can be concluded that the students have fair motivation in learning English because it is effective by the teacher, parents and environment.